The Opening of the European Electricity Market and Environmental Policy: Does the Degree of Competition Matter? - Andrea Bigano; Stef Proost (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper studies the relevance of strategic trade effects in the environmental policy for the European electricity sector. The production, investment and trade of electricity are modelled for four European countries. Three market regimes are distinguished: perfect competition, price regulation and Cournot competition. The model is used to examine the effect of the degree of competition on the state of the environment and to study the strategic trade effects of unilateral environmental policies.
Keywords: L94; F18; D43; 330; Electricity; Trade and the Environment; Elektrizitätswirtschaft; Umweltpolitik; Strategische Handelspolitik; Vollkommener Wettbewerb; Preisregulierung; Wohlfahrtsanalyse; Belgien; Deutschland; Frankreich; Niederlande